Impact of E-Commerce Investment and Enterprise Performance Based on Customer Relationship Management - Azeem, Sana; Nasir, Nadia; Kousar, Shazia; Sabir , Saba (International Journal of Psychosocial Rehabilitation, 2020)
In the current dynamic and complex, competitive environment, the implementation of enterprise e-commerce plays an important role in the development of external business process activities. Through the Internet, information sharing and business process collaboration between enterprises and customers can be realized. This kind of e-service activity based on the e-commerce process is particularly important for customers. However, many business managers have some doubts about the implementation of customer-service-oriented online business activities, because customer service-oriented online business activities need a lot of IT investment, and the performance of this e-business activities is not easy to measure. Therefore, whether the internal e-commerce ability of internal e-commerce implementation and the external e-commerce ability of customer-service-oriented external e-commerce activities can bring performance to enterprises has become a hot issue in the development of enterprise e-commerce. This study provides effective e-commerce implementation strategies for enterprise managers, which has important practical management significance. This paper focuses on the relationship between internal and external e-commerce capabilities and performance and discusses the driving effect of customer-service-oriented e-commerce capabilities on its value. This paper studies the impact of customer relationship management capabilities on the relationship between e-commerce investment and enterprise performance. First, the relationship between E-B capabilities and CRM capabilities is tested. On this basis, the relationship between CRM ability and e-commerce investment, e- commerce ability and enterprise performance is studied. The results show that E-B is positively correlated with CRM (β = 0.345, t = 4.445, P < 0.05; β = 0.382, t = 4.997, P < 0.05; β = 0.274, t = 3.449, P < 0.05; β = 0.341, t = 4.380, P < 0.05; β =0.205, t = 2.535, P < 0.05).